ANALISIS NUMERIK DAN EKSPERIMEN PERFORMA KELAIKAN TABRAK CRASH BOX BERPENAMPANG TOP-HAT MULTICORNER - Naafi'an, Ilman
Nowadays, transportation become one of the most needed aspect in human life. One of the most important concern of vehicle usage is the passenger safety. Both of air, land, and even sea transportation mode requires a system to protect the passenger from the possibility of getting injured or even die during the accident. As the time passed by, the thin-walled structures have been developed. This thin-walled structure in vehicle known as crash box that is used for the energy absorption when the vehicle crashed. The application of crash box in vehicle can reduce the chance of injury and death to passengers. One of the crash boxes that is developed at this time is a top-hat multicorner crash box. This undergraduate thesis explains numerical and experiment analysis about the crashworthiness parameters of the top-hat multicorner crash box that is given a bending impact with a low velocity using 3 points bending methods. This undergraduate thesis also explained about the variation of the distance between the crash box supports and its effects to the crashworthiness parameters. The results of the simulation shows that the numerical model with manufacture effect has a good correlation with the experiment result.